Information and Communication Technologies and Regional Policy: What Can We Learn from Evaluations of Policy Instruments - Walter Scherrer (Central European Public Administration Review)
ICT shall continue to be a driver of economic growth but as the diffusion process does not occur evenly across regions and the potential gains are not evenly distributed across regions, economic policy is challenged at the regional level. But what is the scope of regional economic policy in order to shape the regional economic impact of ICT? Within this context the results of the empirical investigations of five regional economic policy instruments which have been implemented in Salzburg are reviewed. The performance of the policy interventions has been a mixed one. It is concluded that a key element which determines the scope for regional policy and its success is its appropriate relation to policy at the federal level, and that public expenditure has to be adequately complemented for a policy intervention to become successful.